The Use Of Accounting Information To Achieve Millennial Generation Business Success - Novrida Qudsi Lutfillah; Ertin Mega Endina; Bakhrudin Bakhrudin (Politeknik Keuangan Negara STAN, 2022)
This study aims to determine the usefulness of accounting information in decision making in order to achieve business success for the millennial generationas a MSMEs owner. JeThis type of research is a qualitative research with an interpretive approach. In-depth interviews were conducted with three millennial generation informants who own food and beauty services businesses. The results showed that the usefulness of accounting information derived from the financial statements version of Diva, Ninda and Andist had different needs. for Diva, the owner of the getuk business, it helps to minimize mistakes in making decisions in the future. For Ninda, the siomay business owner believes in the benefits of accounting to evaluate performance in a period, Other factors that need to be considered are situational factors, conditions and ways of doing marketing.